Behind the US-China Cold War. (January 2022) - Harris, Jerry
As the global pandemic accelerates economic problems, divisions over global capitalism have sharpened. This includes those who want to delink the US/China relationship, those who wish to recalibrate but maintain the transnational system, and China's own more assertive strategy as its economic power increases. These debates affect national and world politics as antagonism grows, even as capital continues to pour into China.